2022
DOI: 10.31234/osf.io/sg3aw
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Meaningfulness of Effort: Deriving Purpose from Really Trying

Abstract: Effort is costly. It can also be rewarding, however, adding value. Here, we explore effort as a source of meaning in peoples’ lives. Across five samples (N = 1,468), we developed and tested a scale measuring the meaning individuals derive from their efforts, called the Meaningfulness of Effort Scale.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 89 publications
0
7
0
Order By: Relevance
“…We also explored three individual difference variables. Participants completed: The need for cognition scale (Cacioppo & Petty, 1982) that measures individual differences in enjoyment of cognitive effort, the meaningfulness of effort scale (Campbell et al, 2022) that measures the degree to which people find pushing themselves to be meaningful, and the boredom proneness scale (Struk et al, 2017) that measures propensity to feel bored. In Studies 10–12, participants also completed the social desirability scale (He et al, 2015) that measures the tendency to respond in ways that are viewed as favorable by other people.…”
Section: Methodsmentioning
confidence: 99%
“…We also explored three individual difference variables. Participants completed: The need for cognition scale (Cacioppo & Petty, 1982) that measures individual differences in enjoyment of cognitive effort, the meaningfulness of effort scale (Campbell et al, 2022) that measures the degree to which people find pushing themselves to be meaningful, and the boredom proneness scale (Struk et al, 2017) that measures propensity to feel bored. In Studies 10–12, participants also completed the social desirability scale (He et al, 2015) that measures the tendency to respond in ways that are viewed as favorable by other people.…”
Section: Methodsmentioning
confidence: 99%
“…For example, young children may be unmotivated to perform well in the lab and in the classroom because they do not trust that their efforts will pay off or they do not see the activities as relevant to their lives (Matthews, 2018;Michaelson & Munakata, 2021). Children, like adults, may not find the effort required to perform well on assessments of executive function meaningful (Campbell et al, 2022). An extension of this interpretation is that relationships between executive function task performance and academic achievement are partially driven by a willingness to engage executive functions, rather than executive function capacities directly.…”
Section: Reinforcing Executive Function Engagement Within Contextsmentioning
confidence: 99%
“…In another series of lab studies, people reported that symbol-counting and Stroop color-naming were both more effortful and meaningful than passively watching the same symbols or Stroop color-words [3]. What is more, the more effort they applied, the more meaning they derived [9]. Again, there is nothing inherently meaningful about counting symbols or naming colors.…”
Section: Beyond "Because It's There"mentioning
confidence: 99%
“…Again, there is nothing inherently meaningful about counting symbols or naming colors. Yet, the more people pushed themselves, the more meaning they derived from these mundane task [9].…”
Section: Beyond "Because It's There"mentioning
confidence: 99%
See 1 more Smart Citation